(untitled) (Journal of history-rus, 2022)
The study of the historiography of the Pashtun culture of Pakistan has not only a great scientific, but also an undisputed political and practical meaning. Although the Pashtun culture is specific and peculiar, the research world hasn’t paid a sufficient amount of attention to this problem. Currently, there are indirect works on the Pashtun culture of Pakistan in the historical literature, that are related to the national identity, regional and cultural features, as well as the problems that carry religious-ideological character. The given factual historiographical material, which was assembled from the works of Western and Russian-speaking researchers, along with the materials of domestic scientists, paves the ways to concurrently identify the main trends in the socio-political and cultural development of the Pakistani Pashtuns. Taking the features of the studied material into consideration, that predominantly affect religiously-cultural nature of the Afghanistan Pashtuns compared to the Pashtuns of Pakistan, it can be stated that the majority of authors perceive the problem either one-sidedly or ideologically. Nevertheless, the specific features of the Pashtuns at various stages of their Modern and Contemporary history enable the track of the transformation of their cultural development with the Baluchis of Pakistan and mainly illustrate the role of Islam in their life. The study of the historiography of the Pashtuns culture of Pakistan has still not been the subject of a scrutinization, hence, the aim of this study is a comparative analysis of Western, Russian-speaking and domestic works that outline their characteristics. During the research process, the method of Periodization has been applied, which incorporates an appeal to various methods of historical research, videlicet: method of terminological analysis, chronological, statistical, method of biographical and situational analysis. Key words: Pakistan, Pashtuns, culture, historiography, national identity.